Jorge C. Bocobo his life and ideas as educator and jurist - Olivar, Celia Bocobo 1920-
This study presents the life and accomplishments of Dr. Jorge C. Bocobo, fifth president of the University of the Philippines. This is a historical research on the life of Dr. Bocobo and his contributions to education and laws in the Philippines and an analysis on his ideas based upon its socio-psychological, cultural context.